Improving English Learning Motivation With the English App Duolingo - Salsabila Lahji (Morfologi : Jurnal Ilmu Pendidikan, Bahasa, Sastra dan Budaya, 2024)
This qualitative study investigates the effectiveness of the Duolingo English app in enhancing English learning motivation among 11th-grade students at SMK Negeri 1 Sawan. Motivation in language learning is a critical factor influencing proficiency and engagement. Utilizing semi-structured interviews and participant observation, this research explores how the app influences students' intrinsic and extrinsic motivation levels. Findings reveal that DuoLingo positively impacts motivation through its interactive features and gamified learning approach, fostering a more engaging and enjoyable learning environment. Educational implications and recommendations for integrating such technology into language classrooms are discussed.